2023
DOI: 10.1002/brb3.2888
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and stroke: A Mendelian randomization study

Abstract: Background and purpose: Periodontitis has been implicated in the incidence of ischemic stroke. However, the generalizability of results to individuals with different subtypes of periodontitis is unknown. We aimed to investigate the causal relationship of chronic periodontitis (CP) and aggressive periodontitis (AgP) with ischemic stroke and its subtypes in the Mendelian randomization framework. Methods:The genetic proxies of CP were derived from large-scale summary statistics from the UK Biobank datasets (950 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Different populations have different genetic characteristics, and some genetic variations may be prevalent in one population but scarce or absent in another as a result of recent emergence and limited dissemination [ 27 , 28 ]. Hence, the generalizability of our results to other ethnic groups may be potentially limited, and this is also a common limitation in MR studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different populations have different genetic characteristics, and some genetic variations may be prevalent in one population but scarce or absent in another as a result of recent emergence and limited dissemination [ 27 , 28 ]. Hence, the generalizability of our results to other ethnic groups may be potentially limited, and this is also a common limitation in MR studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unlike animal experiments, the MR method reduces the burden of random verification on humans and can demonstrate causality without putting participants at risk [55]. Several MR studies on stroke were previously performed with various results [19,[56][57][58][59]. Smoking behavior was a causal factor for ischemic stroke in an MR analysis [20], and another MR study showed that smoking, body mass index, and waist/hip ratio were causally associated with stroke [21].…”
Section: Discussionmentioning
confidence: 99%
“…Розвиток порушень мінерального обміну при агресивних формах пародонтиту у різних вікових групах потребує подальшого вивчення, при цьому, для розуміння можливих шляхів дослідження набувають актуальності дані, отримані молекулярними генетиками [22,23].…”
Section: епідеміологія і етіопатогенетичні фактори розвитку агресивни...unclassified